NILAI MORAL DALAM CERITA RAKYAT SERPAH BUAYA DAERAH PUNGGUR BESAR KABUPATEN KUBU RAYA - Nisa, Wulan Khairun; Priyadi, Antonius Totok; Wartiningsih, Agus (Universitas Tanjungpura, 2024)
This research aims and is motivated by the idea of documenting the oral literature of the Malay community in the Punggur Besar area, Sungai Kakap sub-district, Kubu Raya regency. The problem in this research is what are the moral values of the community regarding the Serapah Buaya folklore in the Punggur Besar area, Sungai Kakap District, Kubu Raya Regency. The research method used is descriptive, a qualitative form of research and the approach used is the sociology of literary works. The data source in this research is the folklore text Serapah Buaya. There are four techniques used in this research, namely direct research involvement techniques, interview techniques, recording techniques, and recording techniques. The data collection tool is the researcher himself as the key instrument with the assistance of several supporting tools, namely a list of questions, a voice recorder, camera, laptop and stationery. The results of the analysis of research data regarding moral values, there are four moral values reflected in the Serapah Buaya folklore and one implementation of research on learning in schools, namely (1) Moral values of human relationship with God, namely (gratitude, prayer, and steadfastness) (2) The moral values of human relationships with themselves are (self-esteem, fear and obligation towards oneself) (3) The moral values of human relationships with other humans, namely (helping others, helping the weak selflessly, and respecting each other) (4) Moral values human relationship with the natural environment, namely (loving animals and plants).